Pengelolaan tuberkulosis paru melalui peran pos TB di Desa Teluk Paman Kecamatan Kampar Kiri - Zahtamal Zahtamal; Tuti Restuastuti; Fifiz Chandra; Sri Melati Munir; Ridha Restila (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
Tuberculosis (TB) is still a threat to the community in Teluk Paman Village, Kampar Kiri District, Kampar Regency. In addition, it is not yet optimal for community empowerment by the government and health workers. This is indicated by the absence of a